Peer supervision in coaching and mentoring : a versatile guide for reflective practice /: a versatile guide for reflective practice. (2018) - (Master certified coach), Turner, Tammy; Lucas, Michelle; (Executive coaching consultant), Whitaker, Carol
No abstract available